2010
DOI: 10.1017/s0266462310000097
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rational use of cholinesterase inhibitors for Alzheimer's disease in Brazil: Public health strategy combining guideline with peer-review of prescriptions

Abstract: The public health strategy of using expert-review of prescriptions and their compliance to national guideline revealed a low rate of rational use of CHEIs for dementia. Such a strategy is relevant for protecting patients from unproven medical interventions and for reducing waste of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…Como consequência, 38% dos processos de solicitação de IChE não foram deferidos, sendo uma prevalência alarmante se comparada ao não deferimento de outros medicamentos solicitados junto ao CEAF como, por exemplo, imunossupressores (0,7%) 34 . Em um estudo realizado no Rio Grande do Sul, observouse que 62% dos processos de solicitação de IChE para a doença de Alzheimer não foram deferidos e que as principais razões foram a presença de outras demências não-Alzheimer e diagnóstico de demência grave 35 . Uma possível explicação para o não cumprimento dos critérios do protocolo observado no presente estudo é o fato de que o PCDT do Estado de Minas Gerais 11 inclui critérios adicionais de avaliação em relação ao PCDT nacional, com o objetivo de aumentar a especificidade e melhorar a acurácia diagnóstica, a fim de diminuir os custos para o estado ao identificar erros diagnósticos ou grau avançado da doença de Alzheimer (CDR3) que sabidamente não se beneficia do tratamento.…”
Section: Macrorregião Da Grsunclassified
See 1 more Smart Citation
“…Como consequência, 38% dos processos de solicitação de IChE não foram deferidos, sendo uma prevalência alarmante se comparada ao não deferimento de outros medicamentos solicitados junto ao CEAF como, por exemplo, imunossupressores (0,7%) 34 . Em um estudo realizado no Rio Grande do Sul, observouse que 62% dos processos de solicitação de IChE para a doença de Alzheimer não foram deferidos e que as principais razões foram a presença de outras demências não-Alzheimer e diagnóstico de demência grave 35 . Uma possível explicação para o não cumprimento dos critérios do protocolo observado no presente estudo é o fato de que o PCDT do Estado de Minas Gerais 11 inclui critérios adicionais de avaliação em relação ao PCDT nacional, com o objetivo de aumentar a especificidade e melhorar a acurácia diagnóstica, a fim de diminuir os custos para o estado ao identificar erros diagnósticos ou grau avançado da doença de Alzheimer (CDR3) que sabidamente não se beneficia do tratamento.…”
Section: Macrorregião Da Grsunclassified
“…Prescritores com menor tempo de profissão apresentaram maior obediência ao PCDT e tiveram mais solicitações atendidas, sendo este o mesmo resultado encontrado pelo estudo realizado no Rio Grande do Sul 35 . Trata-se de um achado pouco investigado na literatura, mas pode sugerir que médicos com maior tempo de prática tenham dificuldade para cumprir o protocolo devido a hábitos ou costumes, chamados por outros autores como "inércia da práti-ca anterior" 36 , ou ainda, que profissionais mais jovens tenham maior acesso e credibilidade às evidências do PCDT.…”
Section: Macrorregião Da Grsunclassified
“…We considered possible factors that have prevented the Brazilian government's goal being reached. First, concerning the differences between the treatment rates of dementia and AD, we highlight that cholinesterase inhibitors, available free of cost in Brazil, are only provided to patients who fulfill the clinical diagnostic criteria established by the Brazilian guidelines for AD and not to patients with other types of dementia 18 . This may have influenced the differences found in the present study between the treatment for dementia syndromes (9.7%) and for AD (16.1%).…”
mentioning
confidence: 99%
“…Nevertheless, previous randomized trials have revealed that long-term use of Ginkgo Biloba extract did not reduce the risk of AD's progression when compared with a placebo 20,21 . Third, treatment with cholinesterase inhibitors needs periodic reevaluation, every six months, to analyze the drug's effectiveness 18 . If the patient has shown no improvement in, or stagnation of, his or her condition, the medication could be discontinued, as well as if cognition has been severely impaired (very low scores on the MiniMental State Examination) 22 .…”
mentioning
confidence: 99%
“…A previous Brazilian study assessed compliance with the PCDTDA. 11 Only one in four requests for inclusion in the PCDTDA were in accordance with the guidelines. Most requests were from patients with dementia due to Parkinson's disease and vascular dementia (off-label use).…”
Section: Discussionmentioning
confidence: 99%